Preferences through the centennial user experience in mobile food delivery applications - Alvarez Salazar, Cristian Patricio; Coyago Loayza, Ximena Solange; Sarmiento Chugcho, Carlos Bolivar (Revista Universidad de Guayaquil, 2024)
This study was carried out to analyze preferences through user experience in the behavior of Centennials regarding the use of mobile food delivery applications. To collect the data, 3,080 choices were derived using a full factorial design, from a combination of three attributes and three levels each. Of the complete 243 profiles, 13 profiles were selected using an orthogonal design. To present the preferences of the respondents, the technique of shuffling cards was used. The calculation of the respondents' scores was carried out using the Choice Based Conjoint (CBC) method, the statistical treatment was carried out using the R statistical software. The users consulted did not value positively: the intuitive environments, opening hours, monitoring until delivery, while they are receptive to the remaining attributes by levels, we could define a mostly accepted profile, as a user who wants a practical and intuitive application, that has a menu with photos, an application where an estimated delivery time is indicated of the order, as well as an application that introduces you to all restaurants that have promotions and an application that accepts all forms of payment.
Keywords: Users; app; CBC; delivery